Wolbachia Strain wGri From the Tea Geometrid Moth Ectropis grisescens Contributes to Its Host’s Fecundity - Zhang, Yong; Liu, Song; Jiang, Rui; Zhang, Chen; Gao, Tian; Wang, Yun; Liu, Cui; Long, Yanhua; Zhang, Yinglao; Yang, Yunqiu (Frontiers in Microbiology, 2021)
Members of the Wolbachia genus manipulate insect–host reproduction, and are the most abundant bacterial endosymbionts of insects. The tea geometrid moth Ectropis grisescens (Warren) (Lepidoptera: Geometridae) is the most devastating insect pest of tea plants in China and infests thousands of hectares of tea crops annually. In this study, we used a non-culture method to compare the gut bacteria of E. grisescens and other tea geometridae moths. The results showed that the composition of core gut bacteria in larvae of the three geometridae moth species was similar, except for the presence of Wolbachia. A Wolbachia strain was isolated from E. grisescens and designated as wGri. Comparative analyses showed that this strain shared multilocus sequence types and Wolbachia surface protein hypervariable region profiles with cytoplasmic incompatibility (CI)-inducing strains in supergroup B; however, the wGri-associated phenotypes were undetermined. A reciprocal cross analysis showed that Wolbachia-uninfected females mated with infected males resulted in 100% embryo mortality (0% eggs hatched per female). Eggs produced by mating between uninfected males and infected females hatched normally. These findings indicated that wGri induces strong unidirectional CI in E. grisescens. Additionally, compared with uninfected females, Wolbachia-infected females produced approximately 30%–40% more eggs. Together, these results show that this Wolbachia strain induces reproductive CI in E. grisescens and enhances the fecundity of its female host. Thus, the fecundity of E. grisescens is correlated with the presence of Wolbachia.